Interdisciplinarity and multivariate approach in scientific research in education - Mejía Mejía, Elías J. (2024)
This article is the product of the review in university repositories of Perú, of the research published in the last five years in which we have found a tendency in which social scientific research, in general, and those carried out in Education, in particular, to assume only the bivariate approach in research. Education is a complex system, so the interdisciplinary paradigm is the epistemologically fundamental multivariate or factorial approach in scientific research in this field. However, no multivariate or factorial research is carried out and almost 99% of the research reviewed is bivariate research, but its authors, to broaden the spectrum of their analyses, have assumed the technique that their authors call 'dimensioning' of the independent variable to generate specific problems, specific objectives and sub-hypotheses. But the curious thing is that a high percentage of these theses 'dimension' the dependent variable, to generate sub hypotheses, which incur in a mathematical absurdity.